Early marriage and adolescent mindset (A case study of early marriages in Donri-Donri Subdistrict, Soppeng Regency) - Ramli, Mauliadi; Rahman, Abdul; Saifuddin, Saifuddin (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This study aims to investigate the mindset of adolescents who marry early and the impacts of early marriages. This is a qualitative descriptive study with a case study design, allowing in-depth exploration of a specific case. Following data collection through interviews, observations, and documentation, data analysis was conducted to understand the context and the characteristics of the case. The research informants were nine people from three adolescent couples who married early. The location and informants in this research were identified using a purposive sampling technique. The results of the study showed that: adolescent mindset is divided into three processes, namely encoding, storage, and retrieval.  This mindset is shaped by the fulfilling of economic and familial needs, as the majority of adolescents originate from farming families with limited educational backgrounds. The informants underwent the three processes before and after getting married early. The impacts of early marriage include the loss of opportunities for further education, leading to a reduced likelihood of obtaining better jobs and finding the right partner. However, early marriage is negatively perceived by society as it has more negative than positive outcomes.